Methods and Models for Contrastive Textlinguistic Analysis - Vasileva, Silviya (Research Papers, 2021)
The study discusses the existing German language models for contrastive textlinguistic analysis and their application. Its goal and objectives are to cover the pragmatic, textual, syntactic, and lexical linguistic levels in Bulgarian and German. Attention is paid to the concept of comparability: the textual base must be described and analysed so as the reliability and representativeness of the data, obtained through analysis is ensured. The main uniting part of the topic is emphasised considering the ways of its development, the types of topics and their specifics. According to one of the models there are descriptive, explicative, and argumentative structures; the indicators of the text function are also analysed. The problem of denotates and their linguistic expression is discussed as well. An original contrastive model for Bulgarian and German has been created.Exactly this model is the main one in the achieved results and serves as a basis for the creation of specialized didactic texts for the purposes of German language teaching. The main conclusion, taken from the foreign language didactics is the enhancement of linguistic knowledge in its complexity – context and text – in order to perform more efficient linguistic actions.